2019
DOI: 10.4103/aer.aer_95_19
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adding midazolam to bupivacaine for transversus abdominis plane block on postoperative analgesia after hysterectomy: A randomized controlled study

Abstract: Background and Aim:Different adjuncts have been utilized to promote the quality and prolong the duration of local anesthetics for a variety of regional block techniques. This study aimed to assess the effects of midazolam coadministered with bupivacaine in transversus abdominis plane (TAP) block on the 24-h morphine consumption, the postoperative analgesia duration and adverse effects.Settings and Design:A prospective, randomized, controlled double-blind trial that was carried out at a university hospital.Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Sedation scores were evaluated using a sedation scale (0 = awake, 1 = drowsy, 2 = asleep but arousable, 3 = deeply asleep). Patients were considered sedated, if they had a sedation score of > 0 at any time, during the first 24 h after surgery [ 19 ]. Patient satisfaction (area of satisfaction was pain relief) was also assessed in the form of 1 = poor, 2 = moderate, 3 = good, and 4 = perfect [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sedation scores were evaluated using a sedation scale (0 = awake, 1 = drowsy, 2 = asleep but arousable, 3 = deeply asleep). Patients were considered sedated, if they had a sedation score of > 0 at any time, during the first 24 h after surgery [ 19 ]. Patient satisfaction (area of satisfaction was pain relief) was also assessed in the form of 1 = poor, 2 = moderate, 3 = good, and 4 = perfect [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A 2019 prospective randomized control trial by El Kenany and colleagues of this purpose reported a reduction in 24h morphine use and prolongation of postoperative analgesia (47). They assuaged the concern of neurotoxicity through the use of the established dosage of 50 µg/kg of midazolam (but with 20 mL of 0.25% bupivacaine) that has previously been proven to be safe (47). In their 2021 review, Desai et al describe the results for perineural effectiveness of midazolam to be conflicting due to unclear evidence about its benefits over systemic administration (52).…”
Section: Midazolammentioning
confidence: 99%
“…The data for the use of midazolam as an adjunct to local anesthetics in peripheral nerve blocks are limited in the field's current literature landscape (45). Midazolam could be a promising adjuvant owing to its ability to maintain the patient's hemodynamics (unchanged blood pressure and heart rate), relatively low costs, rapid action onset, and metabolic clearance that is better than other benzodiazepines that could warrant its further characterization (46,47).…”
Section: Midazolammentioning
confidence: 99%
See 2 more Smart Citations